Efficient 5-axis CNC trochoidal flank milling of 3D cavities using custom-shaped cutting tools. (October 2022) - Bo, Pengbo; Fan, Hongyu; Bartoň, Michael
Abstract: A novel method for trochoidal flank milling of 3D cavities bounded by free-form surfaces is proposed. Existing 3D trochoidal milling methods use on-market milling tools whose shape is typically cylindrical or conical, and is therefore not well-suited for meeting fine milling tolerances required for finishing of benchmark free-form surfaces like blades or blisks. In contrast, our variational framework incorporates the shape of the tool into the optimization cycle and looks not only for the trochoidal milling paths, but also for the shape of the tool itself. High precision quality is ensured by firstly designing flank milling paths for the side surfaces that delimit the motion space, in which the trochoidal milling paths are further computed. Additionally, the material removal rate is maximized with the cutter–workpiece engagement being constrained under a given tolerance. Our framework also supports multi-layer approach that is necessary to handle deep cavities. The ability and efficacy of the proposed method are demonstrated by several industrial benchmarks, showing that our approach meets fine machining tolerances using only a few trochoidal paths. Graphical abstract: Highlights: Tool shape is optimized in TR milling of 3D cavities bounded by free-form surfaces. High precision is ensured by computing flank milling paths for the side surfaces. The material removal rate is maximized with controlled cutter–workpiece engagement. Our framework supports multi-layer approach to handle deep cavities.